2015
DOI: 10.3986/ac.v44i2.801
|View full text |Cite
|
Sign up to set email alerts
|

The neogene-quaternary evolution of the karst landscape of the Veszprém plateau based on the study of Meggyespuszta paleodoline, Hungary

Abstract: IzvlečekUDK 551.435.8(439) Attila János Trájer, Tamás Hammer, Lilla Mlinárik, Ákos Bede-Fazekas & Judit Padisák:: Neogensko-kvartalni razvoj kraškega površja planote Veszprém na osnovi raziskav paleovrtače Meggyespuszta, Madžarska Na osnovi novih stratigrafskih in morfoloških raziskav orišemo geološki razvoj in funkcijo paleovrtače Meggyespuszta. Metode vključujejo geomorfološko modeliranje ter geološko kartiranje in obdelavo podatkov vrtin. Razvoj topografije vrtače delimo v tri faze: 1) začetno obdobje zakra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In the southern part, dolomite/limestone debris can be found which probably is the witness of an earlier erosion phase, when the relief was higher and the climate more humid and warmer than in the present era. The geomorphological evolution of the paleodoline had previously been studied and three main phases of the landscape evolution were described (Trájer et al 2015). While in the surrounding area, the erosion cleared previously deposited Neogene and partly the Quaternary sediments, we concluded that the paleodoline as a "time capsule" preserved the major environmental changes of the past in the studied area (Trájer et al 2015) (Table 1).…”
Section: The Study Sitementioning
confidence: 78%
See 4 more Smart Citations
“…In the southern part, dolomite/limestone debris can be found which probably is the witness of an earlier erosion phase, when the relief was higher and the climate more humid and warmer than in the present era. The geomorphological evolution of the paleodoline had previously been studied and three main phases of the landscape evolution were described (Trájer et al 2015). While in the surrounding area, the erosion cleared previously deposited Neogene and partly the Quaternary sediments, we concluded that the paleodoline as a "time capsule" preserved the major environmental changes of the past in the studied area (Trájer et al 2015) (Table 1).…”
Section: The Study Sitementioning
confidence: 78%
“…The studied paleodoline has a wide but asymmetrical water catchment area (Trájer et al 2015) which is not unusual in karstic areas since the water catchment boundaries in karst regions are often fragmented (Bonacci 2004). It was found that pollution affects mainly the south part of the paleodoline.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations